A Test: Hume's Missing Shade of Blue. Issue 3 (September 2015) - Finch, Jonathan
Abstract : This paper discusses a possible test of Hume's 'missing shade of blue' and whether it might be possible to make some empirical progress on the question. Towards this end seventy-two students were tested to see if they could determine the correct color ratios of missing black and white shades ranging from a consecutive gap of two out of 236 possible combinations, to a consecutive gap of ten of out of 236 possible combinations. On the most difficult test, four of the seventy-two students correctly determined a missing shade, though these same four all claimed to have above-average experience with art.